Turning flight simulations of a dragonfly-like flapping wing-body model by the immersed boundary-lattice Boltzmann method. (18th September 2018) - Hino, Harunari; Inamuro, Takaji
Abstract: Turning flights of the dragonfly-like flapping wing-body model in six degrees of freedom are numerically investigated by using the immersed boundary-lattice Boltzmann method. The governing parameters of the problem are the Reynolds number Re, the Froude number Fr, and the non-dimensional mass m . We set the parameters at Re = 200, Fr = 15, and m = 51. First, for making a right turn, we simulate a free flight of the model with a smaller stroke angle of the left wing and a larger stroke angle of the right wing. We find that the model turns to the right and rotates clockwise around the body axis. Secondly, in order to recover the roll angle of the body in a horizontal position, we try to control the roll motion of the model by changing the flapping periods of the left and right wings. Finally, using the above results we try to simulate the turning flight by dynamically changing the stroke angles and the flapping periods of the left and right wings. The turning flight can be successfully simulated by a simple control of the stroke angles and the flapping periods of the left and right wings.